Correlation of bacterial community with phosphorus fraction drives discovery of Actinobacteria involved soil phosphorus transformation during the trichlorfon degradation. (1st June 2022) - Wang, Peiying; Li, Qiqiang; Ge, Fei; Li, Feng; Liu, Yun; Deng, Songqiang; Zhang, Dayi; Tian, Jiang
Abstract: Trichlorfon (TCF) is a broad-spectrum phosphorus (P)-containing pesticide, yet its effects on soil P fraction transformation and bacterial communities during the TCF degradation in soils is unknown. In this study, we investigated soil TCF degradation behavior at different contents of 50, 100 and 200 mg/kg, and analyzed residual TCF contents and metabolites by gas chromatography mass spectrometry after 216-h incubation. Our results suggested that TCF was gradually degraded in soils and was be initially hydrolyzed to dichlorvos via P–C bond cleavage and then other P-containing metabolites. By analyzing different P fractions and soil microbial community composition, we found significant increases of soil available phosphorus contents from 2.76 mg/kg (control) to 3.23 mg/kg (TCF-50), 5.12 mg/kg (TCF-100) and 5.72 mg/kg (TCF-200), respectively. Inorganic CaCl2 –P was easily and instantly transformed to primary mineral inorganic P (Pi ) forms of HCl–P and citrate-P, while the proportion of enzyme-P (a labile organic P) fluctuated throughout TCF degradation process. Soil available P contents and Pi fractions were significantly correlated with the relative abundance of Actinobacteria . These results highlighted that Actinobacteria is the dominant soil species utilizing TCF as P sources to increase its community richness, and subsequently affect the transformation of P fractions to regulate soil P cycle. Our study gives new understanding on the microorganisms can involve soil P transformation during organophosphorus pesticides degradation in soils, highlighting the importance of bacteria in P transformation and pesticides soil decontamination. Graphical abstract: Image 1 Highlights: Soil phosphorus fractions transformation was affected by Trichlorfon addition. Soil bacteria could utilize Trichlorfon and its metabolites as phosphorus sources. Actinobacteria was the major soil bacteria to mobilize labile inorganic phosphorus.